Implementing patient navigator programmes within a hospital setting in Toronto, Canada: A qualitative interview study. Issue 4 (October 2022) - Kokorelias, Kristina M; Gould, Sarah; Das Gupta, Tracey; Ziegler, Naomi; Cass, Dan; Hitzig, Sander L
Objectives: This study sought to identify the organisation and system level barriers and facilitators influencing the implementation of patient navigator programmes in one acute care hospital system in Toronto, Canada. Methods: A qualitative descriptive approach informed by the Consolidated Framework for Implementation Research. Data were collected using in-depth interviews and analysed thematically. Results: Thirty-eight individuals participated in interviews (17 community, 21 acute care hospital), including 24 frontline clinicians and 14 programme directors, health care leaders and managers. Implementation of patient navigator programmes was dependent on: (1) a clear consensus on the unique need for patient navigators; (2) champions to promote patient navigation; (3) programme ownership and accountability; (4) external system and organisational landscape and (5) implementation climate. Appropriate mechanisms of communication were found to have impacted each factor as a barrier or facilitator to programme implementation. Conclusion: Strategies for implementing patient navigator programmes into hospital clinical practice should include incorporating evidence to support the programme, considering mechanisms to enable collaborative communication, and the integration of frameworks to facilitate programme integration into the current practices within the organisation.